Caracterização morfológica dos estádios de desenvolvimento do aparelho reprodutor masculino da rã-touro, Rana catesbeiana, no sistema Anfigranja de criação intensiva - Costa, Cristina Lúcia Sant'ana; Lima, Samuel Lopes; Andrade, Dálcio Ricardo; Agostinho, Cláudio Ângelo [UNESP] (My University, 1998)
The objective of this work was to caracterize the morphological characterization of the development stages of male reproduction apparel of bullfrog Rana catesbeiana from intensive Anfigranja system. During the period of one year, 657 bullfrog males were removed from regrowing and reproduction sections in Anfigranja system to study basic aspects of the reproduction of this specie. The collections were realized monthly and, in that occasion, the body and testicles weights for each animal were recorded and their macroscopic gonadal characteristics, registred. Testicles from 274 males were removed and histologically analyzed. From the macro and microscopic gonadal characteristics, analysis set of the testicles, five stages of gonadal maturation for the male of Rana catesbeiana were determined: juvenile, beginning of maturation, intermediate maturation, advanced maturation and spent.
Morphological characterization of development stages of male reproduction apparel of bullfrog, Rana catesbeiana, in the intensive Anfigranja system
Keywords: Captivity; Males gonads bullfrog; Reproduction; Stages